Urea-straw compound base slow-release type powder mulch and its preparation method

CN122916769APending Publication Date: 2026-10-16NANJING FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611147020.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-12
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是由于上述秸秆粉末不具有成膜性,土壤中的热量和水份仍会通过秸秆粉末之间的间隙散失掉,因此将秸秆粉末直接施加到土壤上所产生的保湿和保温效果不好,进而对增加农作物的产量也是相对有限的

Benefits of technology

[0021]This invention utilizes straw, a large amount of waste generated in agricultural production, as raw material to prepare a sprayable powder. This powder can absorb moisture from the soil. Under the action of water molecules, the film-forming substance polyvinyl alcohol in the powder dissolves, and the dissolved polyvinyl alcohol connects the straw powder into a whole composite film. Urea in the powder also dissolves and is slowly released outward under the action of water molecules. Part of the slowly released urea enters the soil as a nutrient to promote crop growth, while a small portion of the urea remaining in the composite film crosslinks the dissolved polyvinyl alcohol polymer chains, giving the composite film a certain degree of water resistance. The formation of the composite film greatly reduces the gaps between the straw powder particles, thereby effectively reducing the outward loss of moisture and heat from the soil. Thus, the resulting straw-based powder mulch film has excellent soil heat preservation and moisture retention effects. This invention endows straw powder with good film-forming properties on the soil surface, has a simple preparation method, realizes the renewable utilization of waste biomass straw resources, and achieves the effect of turning waste into treasure. The experimental results of the efficacy examples demonstrate that the slow-release urea-type sprayable straw-based powder mulch film prepared by this invention is indeed sprayable, convenient and quick to use, and reduces construction costs. The product also has a film-forming function on the soil surface, thereby achieving water retention and heat preservation effects on the soil. Furthermore, the product also has a slow-release urea function, resulting in a significant increase in vegetable yield. This product is called straw-based powder mulch film, a name referencing the naming convention of liquid mulch films. Liquid mulch films are liquid before forming a film on the soil surface, while the product of this invention is straw-based powder before forming a film on the soil surface; therefore, it is referred to here as straw-based powder mulch film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916769A_ABST
    Figure CN122916769A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of urea-straw compound base slow-release powder mulch prepared by using a large amount of agricultural waste straw as raw material. The prepared straw base powder has film forming property, that is, the powder mulch can absorb water in soil, under the action of water molecules, film forming substances in the powder mulch are dissolved, and the straw powder is connected into a whole composite film, the dissolved film forming substances reduce the gap between the straw powder, so that the formed straw base powder mulch has good soil temperature and moisture retention effect; the urea in the powder mulch is also dissolved under the action of water molecules and is released slowly outward, and is crosslinked with the high molecular chain in the film, so that the composite film has a certain water resistance. The powder mulch can be sprayed, the construction difficulty is reduced, the preparation method is simple, and the powder mulch has the urea slow-release function, which is helpful to improve the yield of green vegetables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention provides a urea-straw composite-based slow-release powder mulch film, and also provides a method for preparing the powder mulch film, belonging to the fields of agricultural fertilizers and mulch films. Background Technology

[0002] Currently, polyethylene (PE) is the most commonly used plastic film in agricultural production. It is estimated that over 128,652 square kilometers of agricultural land worldwide is covered by PE film. However, PE is difficult to degrade, and its residues lead to the accumulation of microplastics in the soil, reducing soil porosity and aeration, thus causing soil quality deterioration, slowing plant root growth, and severely impacting crop yields. Liquid mulch represents a promising innovative alternative to PE. Liquid mulch is in a liquid state before use and can be sprayed onto the soil surface. After the liquid mulch dries, a thin film naturally forms on the soil surface; this film inhibits the loss of water and heat from the soil. Liquid mulch is generally made of biomass-based film-forming materials, and the biomass-based liquid mulch remaining in the soil gradually degrades after the crop growing season. However, the proportion of biomass material in currently used liquid mulches is generally small, with water accounting for the largest portion (50%-70%). This means that during the transportation and storage of liquid mulch, a large amount of water not only consumes transportation resources but also occupies a significant amount of storage space, which is detrimental from a carbon neutrality perspective. Therefore, it is of practical significance to develop a new type of waterless and biodegradable mulch film material.

[0003] In China, the annual production of crop straw is staggering. In 2022, China's straw production reached 1.04 billion tons, accounting for nearly one-third of the global total. Globally, straw recycling rates are currently low, and straw burning remains widespread. This results in the emission of large amounts of harmful gases into the atmosphere, causing severe air pollution and harming human health. Although mulching agricultural soil with straw is a traditional agricultural technique, the lack of film-forming properties in straw powder allows heat and moisture to dissipate through the gaps between the straw particles. Therefore, directly applying straw powder to the soil provides poor moisture retention and insulation, thus limiting its impact on increasing crop yields. To date, no straw-based powder with good film-forming properties has been developed for use as a mulch film in agricultural production. Summary of the Invention

[0004] To address the problems existing in the prior art, this invention provides a method for preparing a urea-straw composite-based slow-release powder mulch film. This method uses agricultural waste straw as raw material, is low in cost, simple in preparation, and easy to promote and apply in the market.

[0005] The present invention also provides a urea-straw composite-based slow-release powder mulch film. This product can be used as a mulch film, which has the effect of keeping the soil warm and moist, and at the same time, it can be used as a slow-release fertilizer for urea, which can reduce the release rate of urea and continuously provide nitrogen fertilizer for crops.

[0006] The present invention also provides an application of urea-straw composite-based slow-release powder mulch film in agricultural slow-release fertilizers and agricultural mulch films.

[0007] The specific solution of the present invention is as follows:

[0008] A method for preparing a urea-straw composite-based slow-release powder mulch film, the preparation steps of which are as follows:

[0009] (1) Mix straw powder with NaOH solution and stir at room temperature for 0.5-1.5 h at a stirring speed of 100-300 r / min. Then filter the resulting mixture and wash the filtered straw powder repeatedly with water until the filtrate is neutral. Then dry the straw powder at 50-65℃ to constant weight to obtain alkali-treated straw powder. The size of the straw powder is 40-200 mesh, the concentration of NaOH solution is 3.0-6.5 wt%, and the mass ratio of straw powder to NaOH solution is 1:(7-11).

[0010] (2) Stir the alkali-treated straw powder and urea solution obtained in step (1) at room temperature for 0.5-2.5 h at a stirring speed of 50-200 r / min to obtain mixture A, wherein the concentration of urea solution is 5-25 wt% and the mass ratio of alkali-treated straw powder to urea solution is 1:(10-12).

[0011] (3) At room temperature, formaldehyde solution is added dropwise to the mixture A obtained in step (2) while stirring. The dropping rate is 1 drop every 1-5 seconds. After all the formaldehyde solution has been added, the temperature of the mixture is raised to 60-75℃. Then, the mixture is stirred and reacted at this temperature for 1.5-4.0h. After the liquid in the mixture is removed by centrifugation, solid powder B is obtained. The concentration of the formaldehyde solution is 37wt%, the mass ratio of the formaldehyde solution to the mixture A is 1:(9-12), and the stirring speed is 50-100r / min.

[0012] (4) Mix and stir the solid powder B obtained in step (3) with the PVA solution at room temperature for 0.2-1.0 h at a stirring speed of 50-200 r / min. Then filter the resulting mixture and dry the filtered solid at 50-60℃ for 2-5 h to obtain the solid powder as a slow-release urea type sprayable straw-based powder mulch film. The concentration of the PVA solution is 3-15 wt%, and the mass ratio of the solid powder B obtained in step (3) to the PVA solution is 1:(5-9).

[0013] A further design of the present invention is as follows:

[0014] The concentration of the NaOH solution mentioned in step (1) is 5.0 wt%, and the mass ratio of straw powder to NaOH solution is 1:9.

[0015] The concentration of the urea solution mentioned in step (2) is 15wt%, and the mass ratio of the alkali-treated straw powder to the urea solution is 1:11.

[0016] The mass ratio of formaldehyde solution and mixture A in step (3) is 1:10.5.

[0017] The concentration of the PVA solution in step (4) is 9 wt%, and the mass ratio of the solid powder B obtained in step (3) to the PVA solution is 1:7.

[0018] The water used in steps (1)-(4) is deionized water.

[0019] The present invention also provides a method for preparing a urea-straw composite-based slow-release powder mulch film using straw powder as raw material and prepared by the above preparation method, as well as the dual-functional application of the product in agricultural slow-release fertilizer and agricultural mulch film.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] This invention utilizes straw, a large amount of waste generated in agricultural production, as raw material to prepare a sprayable powder. This powder can absorb moisture from the soil. Under the action of water molecules, the film-forming substance polyvinyl alcohol in the powder dissolves, and the dissolved polyvinyl alcohol connects the straw powder into a whole composite film. Urea in the powder also dissolves and is slowly released outward under the action of water molecules. Part of the slowly released urea enters the soil as a nutrient to promote crop growth, while a small portion of the urea remaining in the composite film crosslinks the dissolved polyvinyl alcohol polymer chains, giving the composite film a certain degree of water resistance. The formation of the composite film greatly reduces the gaps between the straw powder particles, thereby effectively reducing the outward loss of moisture and heat from the soil. Thus, the resulting straw-based powder mulch film has excellent soil heat preservation and moisture retention effects. This invention endows straw powder with good film-forming properties on the soil surface, has a simple preparation method, realizes the renewable utilization of waste biomass straw resources, and achieves the effect of turning waste into treasure. The experimental results of the efficacy examples demonstrate that the slow-release urea-type sprayable straw-based powder mulch film prepared by this invention is indeed sprayable, convenient and quick to use, and reduces construction costs. The product also has a film-forming function on the soil surface, thereby achieving water retention and heat preservation effects on the soil. Furthermore, the product also has a slow-release urea function, resulting in a significant increase in vegetable yield. This product is called straw-based powder mulch film, a name referencing the naming convention of liquid mulch films. Liquid mulch films are liquid before forming a film on the soil surface, while the product of this invention is straw-based powder before forming a film on the soil surface; therefore, it is referred to here as straw-based powder mulch film.

[0022] The working principle of this invention is analyzed as follows:

[0023] 1. Step (1) of this invention involves mixing straw powder with NaOH solution. Straw is mainly composed of cellulose, hemicellulose, and lignin molecules, and contains a large number of pores. The alkaline solution can remove wax, pectin, and lignin between cell walls from the surface of the straw powder, thus exposing the fiber pores on the straw surface. (Appendix) Figure 1 Data shows that the pore volume of alkali-treated straw powder (SA) increased by 41.3% compared to that of untreated straw powder (pristine straw), and the former was 6.9% lighter than the latter. This indicates that some substances were indeed dissolved in the straw powder after alkali treatment, and the pores were significantly enlarged.

[0024] 2. Step (2) of this invention involves mixing the alkali-treated straw powder with a urea solution. Because the surface of the alkali-treated straw powder is rich in pores, and the cellulose and hemicellulose molecules on the inner walls of these pores are rich in hydroxyl groups, these straw pores can adsorb urea molecules from the solution, thus forming a mixture containing a urea-straw complex. (Appendix) Figure 1Data shows that the pore volume of straw powder (SU) treated with urea solution in step (2) was reduced by 10.3% compared with the pore volume of straw powder (SA) before treatment, and the mass of the former was increased by 17.16% compared with the latter. This indicates that after urea treatment, the pores of straw powder are filled by adsorbed urea, resulting in a reduction in the pore size and an increase in the mass of straw powder.

[0025] 3. Step (3) of the present invention is to add formaldehyde solution to a mixture containing urea-straw complex.

[0026] In this process, formaldehyde added under heating conditions reacts with urea molecules in the solution to form urea-formaldehyde polymer. This urea-formaldehyde polymer has a certain viscosity, which promotes more urea particles to stick together and fill the surface pores of the straw, thereby forming a formaldehyde-urea-straw composite powder (SUF) with a higher urea content. Figure 1 Data shows that the pore volume of straw powder (SUF) treated with formaldehyde solution in step (3) was reduced by 27.17% compared with the pore volume of straw powder (SU) before treatment, and the mass of the former was increased by 24.95% compared with the latter. This indicates that after the straw powder was treated with formaldehyde solution, the straw pores adsorbed more urea, resulting in a significant reduction in straw pore size and a significant increase in the mass of straw powder.

[0027] 4. Step (4) of this invention involves mixing the formaldehyde-urea-straw composite powder (SUF) obtained in step 3 with a polyvinyl alcohol (PVA) solution. The polar groups in the urea and urea-formaldehyde molecules on the surface of the formaldehyde-urea-straw composite powder can interact with the hydroxyl groups in the PVA molecules, thereby adsorbing PVA onto the surface of the formaldehyde-urea-straw composite powder to form PVA-formaldehyde-urea-straw composite powder (SUFP). (See attached image) Figure 1 Data shows that the pore volume of straw powder (SUFP) treated with PVA solution in step (4) was reduced by 20.9% compared with the pore volume of straw powder (SUF) before treatment, and the mass of the former was increased by 17.97% compared with the latter. This indicates that after the straw powder was treated with PVA solution, the PVA adsorbed on the powder surface and with good film-forming properties blocked the pores on the surface of the straw (SUF).

[0028] The PVA-formaldehyde-urea-straw composite powder (SUFP) prepared in step (4) is used as a buffer.

[0029] This is a urea-releasing, sprayable solid powder precursor for straw-based mulch films. When sprayed onto the soil surface, the soil moisture interacts with the PVA on the powder surface. Water-soluble PVA molecules are initially dissolved, and the dissolved PVA gels between the powder particles interlock, filling the gaps. Water molecules, after dissolving the PVA on the powder surface, further dissolve the urea in the pores of the straw powder. The urea, after being dissolved in water, first enters the dissolved PVA gels. Hydroxyl groups on the PVA polymer chains in the gels form hydrogen bonds with amino groups on the urea molecules, leading to cross-linking of the PVA molecular chains. This cross-linked, three-dimensional network structure of the PVA gel improves its water resistance. Furthermore, the release rate of uncross-linked urea molecules is further reduced when passing through the cross-linked, three-dimensional network structure of the PVA gel, thus enhancing the slow-release performance of the PVA-formaldehyde-urea-straw composite powder. The cross-linked water-resistant PVA adhesive binds the straw powder into a composite film, effectively reducing the rate of water and heat loss from the soil. This results in a better soil insulation and moisture retention effect for the formed slow-release urea-type sprayable straw-based powder mulch film. Attached Figure Description

[0030] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.

[0031] Figure 1 The samples obtained in steps (1)-(4) of Example 3 of this invention are straw powder (SA), urea-straw compound powder (SU), formaldehyde-urea-straw compound powder (SUF), and solid powder of slow-release urea type sprayable straw-based powder mulch film (i.e., PVA-formaldehyde-urea-straw compound powder, SUFP). The mass change rate and pore volume change rate are based on the mass and pore volume of straw powder (Pristine straw) as 100%. A is the mass change rate curve and B is the pore volume change rate curve.

[0032] Figure 2 This is a process flow diagram of the present invention for preparing a slow-release urea-type sprayable straw-based powder mulch film.

[0033] Figure 3This figure shows the cumulative urea release curves of the solid powder of the slow-release urea-type sprayable straw-based powder mulch prepared in Example 3 of the present invention, as well as the samples obtained in Comparative Examples 7-10 and pure urea. The error bars in the figure represent the standard deviation of the mean of the results obtained from three parallel experiments. The labels in the figure are: A for sample of Example 3, B for sample of Comparative Example 7, C for sample of Comparative Example 8, D for sample of Comparative Example 9, E for sample of Comparative Example 10, and F for pure urea sample. Detailed Implementation

[0034] The above-mentioned and other technical features and advantages of the present invention will be described in more detail below with reference to the embodiments. All chemical raw materials used in the following embodiments are commercially available, chemically pure reagents.

[0035] The straw powder was purchased from Sanyou Straw Pellet Co., Ltd. (Jiangsu, China).

[0036] PVA (degree of polymerization 1780; degree of hydrolysis 99%), sodium hydroxide (99%), urea (98%), and formaldehyde solution (37%) were purchased from Aladdin Reagent Co., Ltd. (Shanghai, China).

[0037] The bok choy seeds (Shanghai Qing 305) used in the planting experiment were provided by Shouhe Seed Industry Co., Ltd. (Shandong, China).

[0038] The water used in the following experiments is deionized water.

[0039] Example 1

[0040] A method for preparing a slow-release urea-based sprayable straw-based powder mulch film, comprising the following steps:

[0041] (1) Mix straw powder with NaOH solution and stir at room temperature for 0.5 h at a stirring speed of 300 r / min. Then filter the resulting mixture and wash the filtered straw powder repeatedly with water until the filtrate is neutral. Then dry the straw powder at 50 °C to constant weight to obtain alkali-treated straw powder. The size of the straw powder is 40-80 mesh, the concentration of NaOH solution is 3.0 wt%, and the mass ratio of straw powder to NaOH solution is 1:7.

[0042] (2) Stir the alkali-treated straw powder and urea solution obtained in step (1) at room temperature for 0.5 h at a stirring speed of 200 r / min to obtain mixture A, wherein the concentration of urea solution is 5 wt% and the mass ratio of alkali-treated straw powder to urea solution is 1:10.

[0043] (3) At room temperature, formaldehyde solution is added dropwise to the mixture A obtained in step (2) while stirring. The dropping rate is 1 drop per second. After all the formaldehyde solution has been added, the temperature of the mixture is raised to 60°C. Then, the mixture is stirred and reacted at this temperature for 1.5 hours. After the liquid in the mixture is removed by centrifugation, solid powder B is obtained. The concentration of the formaldehyde solution is 37 wt%, the mass ratio of the formaldehyde solution to the mixture A is 1:9, and the stirring speed is 50 r / min.

[0044] (4) The solid powder B obtained in step (3) is mixed and stirred with the PVA solution at room temperature for 0.2 h at a stirring speed of 50 r / min. Then the resulting mixture is filtered, and the filtered solid is dried at 50 °C for 2 h to obtain the solid powder as a slow-release urea type sprayable straw-based powder mulch film. The concentration of the PVA solution is 3 wt%, and the mass ratio of the solid powder B obtained in step (3) to the PVA solution is 1:5.

[0045] Example 2

[0046] A method for preparing a slow-release urea-based sprayable straw-based powder mulch film, comprising the following steps:

[0047] (1) Mix straw powder with NaOH solution and stir at room temperature for 0.7 h at a stirring speed of 250 r / min. Then filter the resulting mixture and wash the filtered straw powder repeatedly with water until the filtrate is neutral. Then dry the straw powder at 54 °C to constant weight to obtain alkali-treated straw powder. The size of the straw powder is 80-120 mesh, the concentration of NaOH solution is 4.0 wt%, and the mass ratio of straw powder to NaOH solution is 1:8.

[0048] (2) Stir the alkali-treated straw powder and urea solution obtained in step (1) at room temperature for 1.0 h at a stirring speed of 160 r / min to obtain mixture A, wherein the concentration of urea solution is 10 wt% and the mass ratio of alkali-treated straw powder to urea solution is 1:10.5.

[0049] (3) At room temperature, formaldehyde solution is added dropwise to the mixture A obtained in step (2) while stirring. The dropping rate is 1 drop every 2 seconds. After all the formaldehyde solution has been added, the temperature of the mixture is raised to 64°C. Then, the mixture is stirred and reacted at this temperature for 2 hours. After the liquid in the mixture is removed by centrifugation, solid powder B is obtained. The concentration of the formaldehyde solution is 37 wt%, the mass ratio of the formaldehyde solution to the mixture A is 1:9.5, and the stirring speed is 60 r / min.

[0050] (4) The solid powder B obtained in step (3) is mixed and stirred with the PVA solution at room temperature for 0.4 h at a stirring speed of 90 r / min. Then the resulting mixture is filtered, and the filtered solid is dried at 53 °C for 2 h to obtain the solid powder as a slow-release urea type sprayable straw-based powder mulch film. The concentration of the PVA solution is 6 wt%, and the mass ratio of the solid powder B obtained in step (3) to the PVA solution is 1:6.

[0051] Example 3

[0052] A method for preparing a slow-release urea-based sprayable straw-based powder mulch film, comprising the following steps:

[0053] (1) Mix straw powder with NaOH solution and stir at room temperature for 1.0 h at a stirring speed of 200 r / min. Then filter the resulting mixture and wash the filtered straw powder repeatedly with water until the filtrate is neutral. Then dry the straw powder at 58℃ to constant weight to obtain alkali-treated straw powder. The size of the straw powder is 120-140 mesh, the concentration of NaOH solution is 5.0 wt%, and the mass ratio of straw powder to NaOH solution is 1:9.

[0054] (2) Stir the alkali-treated straw powder and urea solution obtained in step (1) at room temperature for 1.5 h at a stirring speed of 120 r / min to obtain mixture A, wherein the concentration of urea solution is 15 wt% and the mass ratio of alkali-treated straw powder to urea solution is 1:11.

[0055] (3) At room temperature, formaldehyde solution is added dropwise to the mixture A obtained in step (2) while stirring. The dropping rate is 1 drop every 3 seconds. After all the formaldehyde solution has been added, the temperature of the mixture is raised to 68°C. Then, the mixture is stirred and reacted at this temperature for 3.0 h. After the liquid in the mixture is removed by centrifugation, solid powder B is obtained. The concentration of the formaldehyde solution is 37 wt%, the mass ratio of the formaldehyde solution to the mixture A is 1:10.5, and the stirring speed is 75 r / min.

[0056] (4) The solid powder B obtained in step (3) is mixed and stirred with the PVA solution at room temperature for 0.6 h at a stirring speed of 130 r / min. Then the resulting mixture is filtered, and the filtered solid is dried at 55 °C for 3 h to obtain the solid powder as a slow-release urea type sprayable straw-based powder mulch film. The concentration of the PVA solution is 9 wt%, and the mass ratio of the solid powder B obtained in step (3) to the PVA solution is 1:7.

[0057] In this embodiment (Example 3), the following solid samples were collected for each step: the straw powder (named pristine straw) used in step (1) and the obtained alkali-treated straw powder (named SA); the mixture A obtained in step (2) was filtered, and the filtered solid powder was dried at 55°C for 2 hours to obtain a solid sample of straw powder treated with urea solution (i.e., urea-straw composite powder, named SU); the solid powder B obtained in step (3) (i.e., formaldehyde-urea-straw composite powder, named SUF); and the solid powder of the slow-release urea type sprayable straw-based powder mulch film obtained in step (4) (i.e., PVA-formaldehyde-urea-straw composite powder, named SUFP). The dried pristine straw powders, SA, SU, SUF and SUFP samples were weighed and tested for pore volume. The test results are attached. Figure 1 As shown.

[0058] Weighing test method: The dried pristine strawpowders, SA, SU, SUF, and SUFP samples were weighed using an electronic balance (Sartorius, US, Japan). The change in mass of the straw powder (with the mass of the pristine strawpowders as 100%) was used to illustrate the evolution of the straw powder mass after treatment with alkali solution, urea solution, formaldehyde solution, and PVA solution in sequence. The change in mass rate = (mass of each treated sample / mass of straw powder) × 100%. Each sample was tested three times, and the average value was taken as the final result.

[0059] Pore ​​volume testing method: Nitrogen adsorption experiments were conducted at 77 K using a fully automated porosimeter (BSD-660, BSD, Beijing, China). The pore volume of pristinestraw powders, SA, SU, SUF, and SUFP samples was determined by the amount of nitrogen adsorbed at a relative pressure (P / P0) of 0.99. The pore volume change rate (with the pore volume of pristine straw powders as 100%) was used to illustrate the evolution of the pore volume of straw powder after sequential treatment with alkaline solution, urea solution, formaldehyde solution, and PVA solution. The pore volume change rate = (pore volume of each treated sample / pore volume of straw powder) × 100%. Each sample was tested three times, and the average value was taken as the final result.

[0060] Example 4

[0061] A method for preparing a slow-release urea-based sprayable straw-based powder mulch film, comprising the following steps:

[0062] (1) Mix straw powder with NaOH solution and stir at room temperature for 1.3 h at a stirring speed of 150 r / min. Then filter the resulting mixture and wash the filtered straw powder repeatedly with water until the filtrate is neutral. Then dry the straw powder at 62 °C to constant weight to obtain alkali-treated straw powder. The size of the straw powder is 140-170 mesh, the concentration of NaOH solution is 5.8 wt%, and the mass ratio of straw powder to NaOH solution is 1:10.

[0063] (2) Stir the alkali-treated straw powder and urea solution obtained in step (1) at room temperature for 2.0 h at a stirring speed of 90 r / min to obtain mixture A, wherein the concentration of urea solution is 20 wt% and the mass ratio of alkali-treated straw powder to urea solution is 1:11.5;

[0064] (3) At room temperature, formaldehyde solution is added dropwise to the mixture A obtained in step (2) while stirring. The dropping rate is 1 drop every 4 seconds. After all the formaldehyde solution has been added, the temperature of the mixture is raised to 72°C. Then, the mixture is stirred and reacted at this temperature for 3.5 hours. After the liquid in the mixture is removed by centrifugation, solid powder B is obtained. The concentration of the formaldehyde solution is 37 wt%, the mass ratio of the formaldehyde solution to the mixture A is 1:11, and the stirring speed is 85 r / min.

[0065] (4) The solid powder B obtained in step (3) is mixed and stirred with the PVA solution at room temperature for 0.8 h at a stirring speed of 170 r / min. Then the resulting mixture is filtered, and the filtered solid is dried at 58 °C for 4 h to obtain the solid powder as a slow-release urea type sprayable straw-based powder mulch film. The concentration of the PVA solution is 12 wt%, and the mass ratio of the solid powder B obtained in step (3) to the PVA solution is 1:8.

[0066] Example 5

[0067] A method for preparing a slow-release urea-based sprayable straw-based powder mulch film, comprising the following steps:

[0068] (1) Mix straw powder with NaOH solution and stir at room temperature for 1.5 h at a stirring speed of 100 r / min. Then filter the resulting mixture and wash the filtered straw powder repeatedly with water until the filtrate is neutral. Then dry the straw powder at 65 °C to constant weight to obtain alkali-treated straw powder. The size of the straw powder is 170-200 mesh, the concentration of NaOH solution is 6.5 wt%, and the mass ratio of straw powder to NaOH solution is 1:11.

[0069] (2) Stir the alkali-treated straw powder and urea solution obtained in step (1) at room temperature for 2.5 h at a stirring speed of 50 r / min to obtain mixture A, wherein the concentration of urea solution is 25 wt% and the mass ratio of alkali-treated straw powder to urea solution is 1:12.

[0070] (3) At room temperature, formaldehyde solution is added dropwise to the mixture A obtained in step (2) while stirring. The dropping rate is 1 drop every 5 seconds. After all the formaldehyde solution has been added, the temperature of the mixture is raised to 75°C. Then, the mixture is stirred and reacted at this temperature for 4.0 h. After the liquid in the mixture is removed by centrifugation, solid powder B is obtained. The concentration of the formaldehyde solution is 37 wt%, the mass ratio of the formaldehyde solution to the mixture A is 1:12, and the stirring speed is 100 r / min.

[0071] (4) The solid powder B obtained in step (3) is mixed and stirred with the PVA solution at room temperature for 1.0 h at a stirring speed of 200 r / min. Then the resulting mixture is filtered, and the filtered solid is dried at 60 °C for 5 h to obtain the solid powder as a slow-release urea type sprayable straw-based powder mulch film. The concentration of the PVA solution is 15 wt%, and the mass ratio of the solid powder B obtained in step (3) to the PVA solution is 1:9.

[0072] Comparative Example 6

[0073] This embodiment prepares a slow-release urea-type sprayable straw-based powder mulch film according to the steps described in Example 3. The difference from Example 3 is that the particle size of the straw powder in step (1) of this embodiment is 20-30 mesh, which is larger than the 40-200 mesh described in the claims of this invention. That is, the particle size of the straw powder used as raw material in Comparative Example 6 is larger. The other preparation steps and reagent dosages are the same as in Example 3.

[0074] Comparative Example 7

[0075] This embodiment prepares a slow-release urea-based sprayable straw-based powder mulch film according to the steps described in Example 3. The difference from Example 3 is that no alkaline solution is used in this embodiment; instead, the straw powder is directly treated with a urea solution. The other preparation steps and reagent dosages are the same as in Example 3. The specific experimental steps are as follows:

[0076] (1) Stir 120-140 mesh straw powder and urea solution at room temperature for 1.5 h at a stirring speed of 120 r / min to obtain mixture A, wherein the concentration of urea solution is 15 wt% and the mass ratio of straw powder to urea solution is 1:11;

[0077] Steps (2) and (3) in this embodiment are the same as steps (3) and (4) in embodiment 3.

[0078] Comparative Example 8

[0079] This embodiment prepares a slow-release urea-type sprayable straw-based powder mulch film according to the steps described in Example 3. The difference from Example 3 is that formaldehyde solution is not used in this embodiment. Other preparation steps and reagent dosages are the same as in Example 3. The specific experimental steps are as follows:

[0080] Steps (1) and (2) in this embodiment are the same as steps (1) and (2) in embodiment 3.

[0081] (3) After centrifugation, the liquid in the mixture A obtained in step (2) is removed to obtain solid powder B;

[0082] Step (4) in this embodiment is the same as step (4) in embodiment 3.

[0083] Comparative Example 9

[0084] This embodiment prepares a slow-release urea-based sprayable straw-based powder mulch film according to the steps described in Example 3. The difference from Example 3 is that PVA solution is not used in this embodiment. The other preparation steps and reagent dosages are the same as in Example 3. The specific experimental steps are as follows:

[0085] Steps (1)-(3) in this embodiment are the same as steps (1)-(3) in embodiment 3.

[0086] (4) The solid powder B obtained in step (3) is mixed and stirred with water at room temperature for 0.6 h at a stirring speed of 130 r / min. The resulting mixture is then filtered, and the filtered solid is dried at 55 °C for 3 h to obtain the solid powder of this embodiment. The mass ratio of the solid powder B obtained in step (3) to water is 1:7.

[0087] Comparative Example 10

[0088] This embodiment prepares a slow-release urea-based sprayable straw-based powder mulch film according to the steps described in Example 3. The difference from Example 3 is that this embodiment does not involve treatment with urea solution and formaldehyde solution. The other preparation steps and reagent dosages are the same as in Example 3. The specific experimental steps are as follows:

[0089] Step (1) in this embodiment is the same as step (1) in embodiment 3.

[0090] (2) The straw powder treated with alkali obtained in step (1) is mixed and stirred with PVA solution at room temperature for 0.6 h at a stirring speed of 130 r / min. Then the resulting mixture is filtered, and the filtered solid is dried at 55 °C for 3 h to obtain the solid powder of this embodiment. The concentration of PVA solution is 9 wt%, and the mass ratio of straw powder treated with alkali obtained in step (1) to PVA solution is 1:7.

[0091] Application Example 11

[0092] In this embodiment, the solid powder of the slow-release urea-type sprayable straw-based powder mulch film obtained in Examples 1-5 and the solid powder samples obtained in Comparative Examples 6-10 were sprayed onto the soil surface for use as agricultural slow-release urea fertilizer and agricultural mulch film. The specific experimental steps are as follows:

[0093] (1) Select a vegetable planting field with longitude: 118.98385532736967° east and latitude: 32.06034538505579° north, and plant green vegetables in the field;

[0094] (2) In May 2023, the field was divided into several plots of 0.5 m × 0.5 m each, with a spacing of 0.1 m between each plot; 30 green vegetable seeds were sown evenly in each plot; then, 5 of the plots were sown with 0.4 kg / m 2 The solid powder of the slow-release urea-type sprayable straw-based powder mulch film obtained in Examples 1-5 was sprayed evenly at the specified dosage. Another field, a bare soil field without any powder spraying, was selected as a control group. Other fields were sprayed with the corresponding samples from the comparative examples at a dosage of 0.4 kg / m². 2 .

[0095] Effect Example

[0096] In this embodiment, the solid powder of the slow-release urea-type sprayable straw-based powder mulch film obtained in Examples 1-5 and the powder samples prepared in Comparative Examples 6-10 were subjected to the following performance tests.

[0097] 1. Sprayability test

[0098] The sprayability of powder samples was tested using a handheld powder coating machine (model JT-12, Yixin Machinery Equipment Manufacturing Co., Ltd., Shandong). The powder coating machine speed was set to 2000 r / min. If 80% of the powder could be sprayed at a distance greater than 100 cm under these conditions, the powder was considered sprayable; otherwise, the powder was not sprayable.

[0099] 2. Soil temperature and humidity test

[0100] Soil temperature testing: The soil temperature at a depth of 5 cm in each field in Application Example 11 was measured using a curved tube geothermometer (Beijing Dingsheng Ronghe Technology Co., Ltd., China). The test was conducted from 14:00 to 16:00 every day for 30 days, and the average temperature during this test period was reported as the value.

[0101] Soil moisture content testing: While measuring soil temperature, 5g of soil was taken from a depth of 5cm in each field. The soil moisture content was measured using the drying method, which involves drying the 5g soil sample at 80°C. The moisture content was then calculated using the formula: Soil moisture content = [(5 - mass of dried soil) / 5] × 100%. The test was conducted every 2 days for 30 days, and the average soil moisture content during this test period was used as the reported value.

[0102] 3. Biodegradability

[0103] The biodegradability test was conducted in the experimental field of Application Example 11. First, the solid powder sample was evenly spread in a petri dish, with a powder layer thickness of 2 mm. Then, water was evenly sprayed onto the powder layer, with a solid powder to water mass ratio of 1:1.5. After the powder layer air-dried to form a film, circular film samples (50 mm in diameter, mass W0) were cut from the dried film and buried in the soil at a depth of 20 cm. On the 100th day, the samples were removed from the soil and repeatedly washed with deionized water until no obvious impurities were found. After drying at 55°C to constant weight, the samples were weighed and the mass was recorded as W. d The biodegradation rate of the sample was calculated using the following formula:

[0104] Biodegradation rate = [(W0 - W)] d ) / W0]×100%

[0105] 4. Test method for sustained-release performance of urea:

[0106] First, prepare the p-dimethylaminobenzaldehyde colorimetric reagent solution: accurately weigh 20.00g of p-dimethylaminobenzaldehyde and dissolve it in 1000mL of anhydrous ethanol.

[0107] Preparation of urea standard solution (1000 μg / mL): Accurately weigh 1.00 g of urea standard, dissolve it in deionized water, transfer it to a 1000 mL volumetric flask, and dilute to volume to obtain the stock solution.

[0108] To plot the absorbance curve of urea standard: Take six 25 mL colorimetric tubes and add 0, 0.50, 1.00, 2.00, 3.00, and 4.00 mL of 1000 μg / mL urea standard solution, respectively. Then, add 10.00, 9.50, 9.00, 8.00, 7.00, and 6.00 mL of distilled water, respectively, to the 10 mL mark. Next, add 10 mL of colorimetric reagent and 4 mL of 2 mol / L sulfuric acid solution to each colorimetric tube, then add distilled water to the 25 mL mark, mix well, and let stand for 10 min. Using the reaction solution from the first colorimetric tube as a reference solution, measure the absorbance of the reaction solutions in each of the six colorimetric tubes at 422 nm (absorbance was measured using a 752 Pro UV-Vis spectrophotometer). Plot the absorbance value on the ordinate and the concentration of the urea standard solution on the abscissa to create a urea standard absorbance curve.

[0109] First, place 2g of solid powder sample into a 60mm long, 10mm inner diameter delivery tube, sealing one end of the tube. Horizontally immerse the delivery tube in a beaker containing 500mL of distilled water, ensuring the center of the delivery tube aligns with the center of the beaker's water surface, keeping the delivery tube parallel to the water surface and 1cm below the water level. Then, place a stir bar in the beaker and position it on a magnetic stirrer, controlling the stirring speed to 10 seconds. -1 The solution temperature was 25°C. To reduce the impact of uneven fluid flow rate in the beaker on the diffusion rate of urea molecules released from the sample at the delivery tube port, the delivery tube was rotated horizontally by 90° every 2 hours. Samples were taken simultaneously from three different locations in the beaker periodically. 5 mL of sample solution was accurately transferred from each location and added to three 25 mL colorimetric tubes. Then, 3 mL of the previously prepared p-dimethylaminobenzaldehyde colorimetric reagent solution was accurately added to each colorimetric tube. The solution was diluted to the mark with distilled water, allowed to stand for 30 min, and then the absorbance was measured at a wavelength of 422 nm. The absorbance of each sample could be used to find the corresponding urea concentration from the urea standard absorbance curve. The average urea concentration at the three different locations was taken as the urea concentration at that sampling time point. After sampling at the three locations at each time point, 15 mL of distilled water was added to the beaker to ensure that the liquid volume in the beaker remained at 500 mL. The urea concentrations at different sampling time points were collected, and the cumulative urea release rate was calculated. The cumulative urea release rate refers to the percentage of urea mass released from a sample over a certain period of time, relative to the sample's mass before release. It is calculated using the following formula: Cumulative urea release rate = (Cumulative urea release mass during a certain release period / Sample mass before release) × 100%

[0110] 5. Vegetable yield test

[0111] After the greens in each field in Application Example 11 have completed one growing season (1 month), the greens, along with their roots, are removed from the field, and the soil attached to the roots is gently brushed off. Then, the total weight of the greens produced in each field is weighed, and the effect of the slow-release urea-type sprayable straw-based powder mulch on the yield of greens is evaluated based on the yield of greens in each field.

[0112] 6. As can be seen from Table 1, the powders prepared in Examples 1-5 and the powders prepared in Comparative Examples 7, 8, and 10 are all sprayable, while the powders obtained in Comparative Examples 6 and 9 are not sprayable. The difference between Comparative Example 6 and Example 3 is that the particle size of the straw powder in step (1) of Comparative Example 6 is 20-30 mesh, which is larger than the 40-200 mesh described in the claims of this invention. That is, the particle size of the straw powder used as raw material in Comparative Example 6 is relatively large. Due to the excessive weight of the powder particles in Comparative Example 6, the spraying distance of most of the powders in Comparative Example 6 did not exceed 100 cm in the sprayability test. The difference between Comparative Example 9 and Example 3 is that Comparative Example 9 did not use PVA solution, while the other preparation steps and reagent amounts were the same as in Example 3. This resulted in the powder surface of Comparative Example 9 being composed of urea molecules instead of PVA. The polar urea molecules have strong hygroscopicity, and the water molecules on the powder surface of Comparative Example 9 caused the powder to agglomerate more easily, thereby reducing the flowability of the powder of Comparative Example 9. This also resulted in most of the powders of Comparative Example 9 not being sprayed more than 100 cm in the sprayability test.

[0113] Table 1 also shows that in Application Example 11, the average soil temperature of the fields sprayed with the powders of Examples 1-5 was 3.8-3.99℃ higher than that of the bare soil fields without any powder spraying; at the same time, the soil moisture content at a depth of 5cm in the former was 12.3-13.1% higher than that in the latter. However, the soil temperature using the sample from Comparative Example 6 was only 0.69℃ higher than that of the bare soil fields without powder spraying; and the soil moisture content at a depth of 5cm in the former was only 1.8% higher than that in the latter. That is, the sample from Comparative Example 6 did not significantly improve soil temperature and soil moisture content. This is because the powder sample from Comparative Example 6 had poor sprayability and did not form an effective cover on the soil, causing heat and moisture to escape from the cracks in the coating, thus failing to provide effective heat and moisture retention for the soil.

[0114] The soil sample from Comparative Example 7 had a soil temperature only 1.56°C higher than that of bare soil without powder spraying; simultaneously, the soil moisture content at a depth of 5 cm in the former was only 2% higher than that in the latter. This indicates that the sample from Comparative Example 7 had a very limited effect on improving soil temperature and moisture content. This is because the difference between Comparative Example 7 and Example 3 is that Comparative Example 7 did not use an alkaline solution; instead, the straw powder was directly treated with a urea solution. An alkaline solution can remove waxes, pectin, and lignin between cell walls from the surface of the straw powder, exposing the fiber pores on the straw surface. Since Comparative Example 7 did not use an alkaline solution to treat the straw powder, the straw powder did not have enough pores to adsorb urea; that is, Comparative Example 7 did not adsorb a sufficient amount of urea. The role of urea is that the amino groups on the urea molecule can form hydrogen bonds with the hydroxyl groups on the dissolved PVA polymer chains, thereby cross-linking the PVA molecular chains. This cross-linking into a three-dimensional network structure of PVA gel improves the water resistance of the resulting composite film (composed of straw powder and the PVA gel between the straw powder particles). Because Comparative Example 7 did not adsorb a sufficient amount of urea, the PVA gel in the composite film was easily dissolved by soil moisture, exposing the voids between the straw powder particles. Heat and moisture in the soil dissipated through these voids, thus Comparative Example 7 did not provide effective soil insulation and moisture retention.

[0115] The soil temperature of the sample from Comparative Example 9 was only 0.27°C higher than that of the bare soil without powder spraying; simultaneously, the soil moisture content at a depth of 5cm in the former was only 0.3% higher than that in the latter. In other words, the sample from Comparative Example 9 did not increase soil temperature or moisture content. This is because the sample from Comparative Example 9 not only has poor sprayability but also does not contain polyvinyl alcohol. Therefore, it did not form any film-forming material to seal the gaps between the solid straw powder particles. This resulted in a significant loss of heat and moisture from the soil through these gaps, thus the sample from Comparative Example 9 did not provide effective soil warming and moisture retention.

[0116] The soil temperature of the sample from Comparative Example 10 was only 1.89°C higher than that of the bare soil without powder spraying; simultaneously, the soil moisture content at a depth of 5cm in the former was only 2.9% higher than that in the latter. This indicates that the sample from Comparative Example 10 had a limited effect on increasing soil temperature and moisture content. This is because the sample from Comparative Example 10 was not treated with urea and formaldehyde solutions. The role of urea is that the amino groups on the urea molecules can form hydrogen bonds with the hydroxyl groups on the dissolved PVA polymer chains, thereby cross-linking the PVA molecular chains. This cross-linking into a three-dimensional network structure of PVA gel improves the water resistance, thus enhancing the water resistance of the resulting composite film (composed of straw powder and PVA gel between straw powder particles). Since Comparative Example 10 did not adsorb urea, the PVA gel in the composite film was dissolved by the soil moisture, exposing the voids between the straw powder particles. Heat and moisture in the soil were then lost through these voids, thus Comparative Example 10 did not provide effective soil insulation and moisture retention. The biodegradability rates of Examples 1-5 in Table 1 all exceeded 85%. This is due to the high biodegradable content of PVA, urea, and straw powder in these samples, indicating that the slow-release urea-type sprayable straw-based powder mulch film prepared by this invention has good biodegradability and environmental friendliness.

[0117] The cumulative urea release rate curve of the sample shows (see attached) Figure 3 The time taken for pure urea to reach a cumulative urea release rate of 100% was less than 3 hours. This is because pure urea samples are readily soluble in water and therefore do not exhibit a significant slow-release effect. In contrast, the sample in Example 3 reached a final and stable cumulative urea release rate of 33%, and the time taken to achieve this rate was greater than 60 hours. This indicates that the sample in Example 3 can adsorb and release approximately 33 wt% of urea and has a significant slow-release effect, making it suitable for use as a slow-release urea fertilizer.

[0118] The cumulative urea release rate of the sample in Comparative Example 7 reached a final and stable rate of 8.2% in 23 hours. This indicates that the sample in Example 7 contained only about 8 wt% of adsorbable and releasable urea. This is because Comparative Example 7 did not use straw powder treated with alkali, resulting in insufficient porosity for urea adsorption. In other words, Comparative Example 7 did not adsorb a sufficient amount of urea. The limited amount of urea released by the sample in Comparative Example 7 provides limited nutrition for crop growth.

[0119] The final and stable cumulative urea release rate of the sample in Comparative Example 8 was 19.9%, and the time to reach this cumulative urea release rate was 36 hours. This indicates that the content of adsorbable and releasable urea in the sample of Comparative Example 8 was 13% lower than that in the sample of Example 3. This is because the difference between Comparative Example 8 and Example 3 is that the sample of Comparative Example 8 did not use formaldehyde solution. Formaldehyde added under heating conditions reacts with urea molecules in the solution to form urea-formaldehyde polymers. These urea-formaldehyde polymers have a certain viscosity, which can promote more urea particles to stick together and fill the surface pores of the straw, thereby forming a formaldehyde-urea-straw complex powder with a higher urea content. Since the sample of Comparative Example 8 did not use formaldehyde solution, the urea content in the sample of Comparative Example 8 was much lower than that in the sample of Example 3.

[0120] The final and stable cumulative urea release rate of the Comparative Example 9 sample was 27.9%, and the time to reach this cumulative urea release rate was 5 hours. This indicates that the sustained-release performance of the Comparative Example 9 sample for urea is significantly lower than that of the Comparative Example 3 sample. This is because the Comparative Example 9 sample did not use a PVA solution, meaning that it lacked a PVA gel coating on the outermost surface of the straw powder. The release rate of urea molecules is further reduced when passing through the cross-linked, three-dimensional network structure of the PVA gel. Because the Comparative Example 9 sample lacks a PVA gel to hinder urea release, its sustained-release performance is also weaker.

[0121] The final and stable cumulative urea release rate of the Comparative Example 10 sample was 0%. This is because the Comparative Example 10 sample was not treated with urea solution and formaldehyde solution, that is, the Comparative Example 10 sample did not contain urea and was not a slow-release urea type material.

[0122] Table 2 lists the effects of Example 3 and the comparative examples on the yield of leafy greens. The data in Table 2 show that the leafy green yield in the field sprayed with the powder sample of Example 3 was 4.15 kg, which was 141% higher than the yield in the bare soil field (1.72 kg) without any powder spraying. In contrast, the yields in the fields corresponding to Comparative Examples 6-10 were only 24.41%, 30.8%, 12.8%, 20.34%, and 22.1% higher than those in the bare soil field, respectively. Therefore, the slow-release urea-type sprayable straw-based powder mulch film of Example 3 significantly increased the yield of leafy greens in the field, confirming the rationality and necessity of preparing the samples according to the steps and corresponding parameter ranges described in the claims.

[0123] Table 1 shows the sprayability results of the solid powders prepared in Examples 1-5 and the powders prepared in Comparative Examples 6-10, and the test results of average soil temperature, average soil moisture content, and biodegradation rate in application example 11, where bare soil samples from the above examples were sprayed on each field plot, and samples from fields without any powder were also sprayed. In the table, "-" indicates that the sample was not tested for the corresponding item, and bare soil refers to fields without any sample from the examples.

[0124] sample Sprayability Average soil temperature (°C) Average soil moisture content (%) Biodegradation rate (%) Example 1 Sprayable 25.03 20.1 88.8 Example 2 Sprayable 25.1 20.4 89.1 Example 3 Sprayable 25.22 20.9 89.3 Example 4 Sprayable 25.09 20.7 88.9 Example 5 Sprayable 25.05 20.3 88.7 Comparative Example 6 Do not spray 21.92 9.6 88.5 Comparative Example 7 Sprayable 22.79 9.8 88.5 Comparative Example 8 Sprayable 24.98 17.2 89.6 Comparative Example 9 Do not spray 21.5 8.1 89.3 Comparative Example 10 Sprayable 23.12 10.7 88.9 bare soil - 21.23 7.8 -

[0125] Table 2 shows the experimental results of vegetable yield in each field plot after spraying the solid powder prepared in Example 3 and the powder prepared in Comparative Examples 6-10, respectively, in Application Example 11. Bare soil indicates fields where no sample from any of the examples was sprayed.

[0126] sample Example 3 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 bare soil Vegetable yield (kg) 4.15 2.14 2.25 1.94 2.07 2.1 1.72

Claims

1. A method for preparing a urea-straw composite-based slow-release powder mulch film, the preparation steps of which are as follows: (1) Mix straw powder with NaOH solution and stir at room temperature for 0.7-1.5 h at a stirring speed of 100-250 r / min. Then filter the resulting mixture and wash the filtered straw powder repeatedly with water until the filtrate is neutral. Then dry the straw powder at 54-65℃ to constant weight to obtain alkali-treated straw powder. The size of the straw powder is 80-200 mesh; (2) The mixture containing urea-straw complex was prepared by the following method: the straw powder treated with alkali obtained in step (1) and the urea solution were stirred at room temperature for 1.0-2.5 h at a stirring speed of 50-200 r / min to obtain mixture A; (3) At room temperature, formaldehyde solution is added dropwise to the mixture A obtained in step (2) while stirring. The dropping rate is 1 drop every 1-5 seconds. After all the formaldehyde solution has been added, the temperature of the mixture is raised to 60-75℃. Then, the mixture is stirred and reacted at this temperature for 1.5-4.0h. After the liquid in the mixture is removed by centrifugation, solid powder B is obtained. The stirring speed is 50-100r / min. (4) Mix and stir the solid powder B obtained in step (3) with the PVA solution at room temperature for 0.2-1.0h at a stirring speed of 50-200r / min. Then filter the resulting mixture and dry the filtered solid at 50-60℃ for 2-5h to obtain the solid powder as a urea-straw composite-based slow-release powder mulch film. The concentration of the NaOH solution mentioned in step (1) is 4.0-6.5 wt%, and the mass ratio of straw powder to NaOH solution is 1:(8-11); The concentration of the urea solution mentioned in step (2) is 10-25 wt%, and the mass ratio of the alkali-treated straw powder to the urea solution is 1:(10.5-12); The concentration of the formaldehyde solution in step (3) is 37 wt%, and the mass ratio of the formaldehyde solution to mixture A is 1:(9-12); The concentration of the PVA solution in step (4) is 3-15 wt%, and the mass ratio of the solid powder B obtained in step (3) to the PVA solution is 1:(5-9).

2. The preparation method according to claim 1, wherein, The water used is deionized water.

3. A urea-straw composite-based slow-release powder mulch film prepared by the preparation method according to any one of claims 1-2.

4. The application of the urea-straw composite-based slow-release powder mulch film as described in claim 3 in agricultural slow-release fertilizers and agricultural mulch films.